Guiding the Way to New Opportunities in the Copán Valley, Honduras - Junho Pena, Maria-Valéria (World Bank, Washington, DC, 2012)
One of the challenges of rural poverty reduction in Latin America is to enhance non-farm economic activity, diversify employment, and foster enterprise activity. Although poverty has decreased over the last decade in Honduras, it continues to be pervasive, particularly in rural areas in the southern and western areas, including the Copan Valley, where the devastating economic impacts of Hurricane Mitch linger. This area contains the Copan Park, one of the most informative and impressive Mayan ruins in Central America with a large quantity of excellently preserved stone sculptures and hieroglyphic texts. This site is an important element in the patrimony of Honduras and the Government is seeking to preserve it for future generations, while increasing the number of tourists to promote sustainable economic development. During 2000-2002, a small, innovative, and successful program was carried out in Copan with support from the IDA-financed Profuturo Project, to help increase employment opportunities and promote research and dissemination of knowledge concerning the world of the Maya. The implementation of this program provides many lessons for development initiatives in areas of tourism growth and rural poverty, particularly among indigenous communities. In coordination with local initiatives and Government support, this program has helped to foster a new perspective on the role that parks such as Copancan play in regional and local development, poverty reduction, and environmental management.